Benefits of Delayed Cord Clamping - Dhakal, Kamala (Journal of Nursing Education of Nepal, 2023)
Delayed cord clamping (DCC) leaves the cord alone after birth and avoids disrupting the  normal birth process. While the cord is pulsating, placental transfusion is supplying the baby  with oxygen, nutrients and an increased blood volume to support the transition to life outside  the womb. Delayed cord clamping confers many benefits to the newborn baby including higher number  of red blood cells, stem cells and immune cells at birth. In premature or compromised babies,  delayed cord clamping may provide essential life support, restore blood volume and protect  against organ damage. It reduces the risk that the baby will have iron deficiency anemia  without substantial side effects in baby.
Keywords: Benefits; Cord Clamping; Delayed